IMPLEMENTASI PEMBUATAN WEBSITE CONTENT MANAGEMENT SYSTEM MENGGUNAKAN WORDPRESS SEBAGAI MEDIA PENYAMPAIAN INFORMASI - Eka Wahyuningsih; Amanda Dewi Puspita; Asep Ahmad Zainudin; Dimas Muhammad Yusup; Ilham Bradja Mukti; Maulayah Hanipah; Muhammad Vicky Pratama; Reza Aldiansyah; Rian Hidayat (Abdi Jurnal Publikasi, 2022)
In the midst of the rampant development of technology and information in marketing in various fields, of course management in building a website is one of the important aspects in showing their quality in selling the products/services they have. One of the most effective promotional media for advertising information is a website, because the website can be reached by all people. This is in line with the increasing graph of internet use in Indonesia from year to year which of course can be maximized by individuals or an institution in self-introduction media and promotional media. With the increasingly widespread use of websites by various people and groups, companies, individuals and government agencies use websites as a media for promotion and introduction. In general, a website is a page that contains certain information and can be accessed by everyone using internet data. Generally websites can be accessed using various search engines such as Google, Yahoo and Bing. Therefore making a website that is attractive and of course easy to understand by users will be an added value in the media for delivering information from the website.